2017
DOI: 10.1103/physrevb.95.094514
|View full text |Cite
|
Sign up to set email alerts
|

Consistent two-lifetime model for spectral functions of superconductors

Abstract: Recently it has been found that models with at least two lifetimes have to be considered when analyzing the angle resolved photoemission data in the nodal region of the cuprates [T. Kondo et al., Nat. Commun. 6, 7699 (2015)]. In this paper we compare two such models. First we show that the phenomenological model used by Kondo et al. violates the sum rule for the occupation number. Next we consider the recently proposed model of the so-called Dynes superconductors, wherein the two lifetimes measure the strengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…ARPES, STM and our own THz data, pointing to "Dynes-superconductor" physics [31][32][33][34][35] But this pair breaking does not originate from magnetic impurities [65], as it does in BCS-Abrikosov-Gorkov theory. In fact the origin of the strong residual (T→0) fermionic Drude response is likely the central mystery in overdoped cuprates.…”
Section: Extensive Pair-breaking Has Been Clearly Observed Inmentioning
confidence: 74%
See 1 more Smart Citation
“…ARPES, STM and our own THz data, pointing to "Dynes-superconductor" physics [31][32][33][34][35] But this pair breaking does not originate from magnetic impurities [65], as it does in BCS-Abrikosov-Gorkov theory. In fact the origin of the strong residual (T→0) fermionic Drude response is likely the central mystery in overdoped cuprates.…”
Section: Extensive Pair-breaking Has Been Clearly Observed Inmentioning
confidence: 74%
“…One way to account for dynamic coexistence of small pairs and free fermions is to postulate massive pair breaking that depletes the superfluid condensate and creates unpaired electrons. At a phenomenological level, this idea has been just patched onto the BCS picture by using the Dynes substitution, E→E -iΓ pb , where Γ pb is the pair-breaking rate [31][32][33][34][35]. Note that this Γ pb is different from and unrelated to the rates of elastic scattering of free fermions, Γ f , and of free (uncondensed) pairs, Γ p , on impurities, defects, phonons, etc.…”
Section: Non-bcs Theoriesmentioning
confidence: 99%
“…Based on Nam's description of the electromagnetic properties of superconductors, 10 in this paper we have presented a comprehensive set of predictions for the optical conductivity of the recently identified Dynes superconductors. 6,7 In particular, we have shown that two metals with the same optical response in the normal state and equal superconducting gaps ∆ may exhibit very different superconducting responses, with the shape of the latter depending on the ratio of the pair-breaking and pair-conserving scattering rates Γ and Γ s , see Fig. 2.…”
Section: Discussionmentioning
confidence: 92%
“…In Ref. 5 we have argued that Eqs. (2,3) represent the simplest internally consistent extension of the BCS theory to superconductors with simultaneously present pair-conserving and pair-breaking processes, and we have called such systems the Dynes superconductors.…”
Section: Introductionmentioning
confidence: 99%